213. Multi-centered Evaluation of an Acute Respiratory Tract Infection Audit-Feedback Intervention: Impact on Antibiotic Prescribing Rates and Patient Outcomes. (26th November 2018) - Madaras-Kelly, Karl; Hruza, Hayli; Pontefract, Benjamin; Mckie, Robert; Hostler, Christopher; Townsend, Mary; Potter, Emily M; Spivak, Emily; Hall, Sarah; Goetz, Matthew; Nevers, McKenna; Ying, Jian; et al.
Abstract: Background: Audit-feedback of antibiotic prescribing rates for acute respiratory infections (ARIs) is a promising approach to reduce antibiotic use; however, the generalizability and sustainability are unknown. We describe an audit-feedback intervention and outcomes across multiple seasons in different clinic settings. Methods: Two VA Medical Centers distributed audit-feedback reports targeting providers with frequent ARI visits in emergency department (ED) and primary care (PC) during 2015–2016 and 2016–2017. An academic detailing visit delivered by local peers accompanied the initial audit-feedback report. The intervention was expanded to ED and PC clinics ( n = 10) in three other VA facilities in 2017–2018. Outcomes included rates of antibiotics prescribed, recurrent visits for ARIs within 30 days, and adverse events. We assessed intervention sustainability in initiating VAs, and intervention generalizability in expansion VAs. Mixed-effect logistic regression models were used to assess intervention effect on antibiotic prescribing and outcomes. Results: Antibiotic prescribing for uncomplicated ARI visits ( n = 7, 814) declined from 53.8% to 27.9% post intervention. The intervention was associated with a reduction in odds of prescribing antibiotics in initiating facilities (odds ratio [OR] 0.6 (95% CI 0.3, 0.9), which declined further with an annual OR 0.8 [95% CI 0.7, 1.1] per year. Preliminary 6-month postintervention results were available from pilot clinics ( n = 3) within two of the expansion VAs, which indicated similar effectiveness (OR 0.5 [0.4, 0.7]). Recurrent visits for ARIs (8.2% vs. 8.6%, P = 0.14) and adverse events (2.3% vs. 2.1%, P = 0.90) were not different pre-/post-intervention. Receipt of an antibiotic was not associated with recurrent visits for ARI (8.6% vs. 8.0%, P = 0.45) or adverse events (1.9% vs. 1.7%, P = 0.11). Conclusion: An audit-feedback intervention sustained a reduction in antibiotic prescribing for ARIs over 3 years, and resulted in similar reductions in antibiotic use in varied ED and PC settings without affecting ARI-related return visit rates. Disclosures: All authors: No reported disclosures.